Improvement model technology intermediate level maintenance of radio-relay equipment - Radonjić, Vojkan M.; Đukić, Slobodan R.; Jovanović, Danko M.; Ćirić, Milenko P. (Vojnotehnički glasnik / Military Technical Courier, 2015)
The work was conducted to investigate the manner of improving the technology of intermediate level maintenance of radio-relay devices. The Improved model of maintenance techniques will be applied in practice during corrective maintenance of radio-relay devices. The results obtained during the application of the proposed model will serve to draw conclusions about the effectiveness of the defined model of maintenance technology. Introduction In the performed research, one technology model for preventive and corrective maintenance of one type of digital radio-relay devices (RRDs) used in the units of the Army of Serbia is improved. Given that the technological operations of preventive maintenance are contained in the corrective maintenance technology, the research gives the model of technology relating to corrective maintenance. The technology model would be realized through the intermediate level maintenance carriers in the Serbian Army (SA) units - logistics battalions. Logistics battalions, in terms of technical maintenance, are the first direct contact with users of RRDs. Therefore, the improved technology model should enable rapid and successful corrective maintenance carried out by logistics battalions in order to achieve higher availability and reliability of RRDs. Maintenance technology Maintenance technology presents organizational and technical solutions that provide clear answers to technology questions: WHAT, WHEN, WHO, WHAT and WHERE to perform maintenance of a technical device. The answers to these questions determine the technology of intermediate-level maintenance of radio-relay devices (RRDs) in the Army of Serbia. A model of the technological process for intermediate level maintenance of RRDs will contain explicit answers to these technology questions. Model of intermediate-level maintenance technology Maintenance technology of a technical device depends exclusively on the design and technical characteristics of the asset. Further research will show the characteristics of the GRC 408E RRD. Characteristics of the GRC 408E RRD in terms of maintenance The GRC 408E family of radio-relay devices belongs to digital multi-channel radio relay devices. It is based on modern technology, electronics, telecommunications and information technology. The integral device modules are: A25A2- DC power supply module, A25A12- AC power module A25A3- display module, A14 - CPU, A13- EOW official channel module, A11- module interface and modem, A1- receiver module, transmitter module A18-, A19- RF filter module, A21- power monitor module and A24A4 amplifier module. The operation of all modules is achieved via the CPU, the A14 module. Assumptions of the technology maintenance model In relation to the structural characteristics of this equipment, preventive maintenance is implemented by the self-test of the device which performs the necessary diagnostic measurements of important parameters. Compared to other maintenance equipment, at the intermediate level maintenance, preventive and corrective maintenance are based on an automatic measurement point, ie. TEST station , which measures all essential parameters of the device. The research will assume that the corrective maintenance at the intermediate level maintenance is realized by replacing the aggregate component modules for faster repair. The technology model for intermediate-level maintenance is not capable of implementing corrective maintenance of RRDs in case of the malfunctioning of the A19- RF filter module and A21- power monitor module due to the structural features of the modules. The device is then sent to a higher level of maintenance. The research assumed that the intermediate level maintenance, either preventive or corrective in character, is implemented in logistics battalions of the Army of Serbia. Maintenance technology model The model of intermediate-level maintenance technology is based on the measurements of RRD important parameters whose comparison with reference valuesrepresents the inspection of a device and its component modules. Also, based on the measurement results, the algorithm for detecting defects in the module functionalty successfully detects and locates the faulty module. Measurements of important signal parameters are realized in two ways. The first method is an implemented self-test method with built-in software for measuring and detecting defects in the functionality of modules, a so-called self-test. Another measuring method is to join an RRD to an automatic measuring point at which around 150 different parameters are measured. Measuring device parameters using the self-test The self-test represents software defect detection of the functional correctness of individual modules in a device with the ultimate goal of diagnosing the status of devices. The self-test software program detects whether each module performs its function, based on the order submitted by the CPU module. There are four forms of the self-test, and their selection is done by an appropriate command offered through a user application, by activating the command to start the self-test. The forms of the test are: TEST PARAMETER SETUP, FIXED PARAMETER TEST LOOP SELECTION FRONT PANEL and TEST. The device parameters measured by the self-test are: the level of the received signal, the BER error in receiving the signal, the level of the transmitted signal, the ratio of active and reflected power, supply voltage modules, external power supplies, transmitting and receiving frequencies, modulation types, interface types, bit rate, network addresses, etc. Measurement of the device parameters by the TEST station The TEST station performs an integrated and software-controlled operation of special measuring instruments. The instruments provide detailed measurements of individual signals within the device by which the modules communicate with each other and realize their primary purpose. The results of measurements are used for two main technological operations of the technology model: defect detection and final measurements and tests. A complete measurement of parameters takes about 60 minutes, during which the instruments measure about 150 parameters important for the analysis of RRD functionality. The TEST station is used for measuring 11 different functions during operation. Based on these functions and the reference values ​​of the measured RRD parameters, a model of an algorithm for defect detection in the component modules is created. The model of the algorithm of RRD defect detection facilitates technical maintenance and accurately directs it - on the basis of the results of the measurement test station, it accurately locates a faulty module or a module that is a potential cause of the RRD malfunction. The proposed defect detection algorithm model is a contribution to easier and more efficient RRD maintenance. Model of the technological process of intermediate level maintenance Model of the technological process of intermediate level maintenance that would be realized in the SA logistics battalions is shown in Figure 7. Application of the maintenance technology model Further research was carried out by applying and testing the effectiveness of the proposed model of the intermediate level maintenance technology. The proposed model of the technological process of intermediate level maintenance and the self-test technological operation gave the results shown in Figure 8. The blackout results show that there is a defect manifested by no RF signal, and the probable causes of defects are A1, A19 or A21 modules. After the application of the technological operations of measurements with the TEST station, the obtained measurement results are partially shown in Table 2. The results show that the measurement by the TEST station is not fully realized due to measurement number 002, which indicates a malfunction of the A25A2 module. Applying the model of the defect detection algorithm, a malfunction of A25A2 DC voltage supply module was found, which differs from the proposed solution of the defect detection during the implementation of the self-test technological operation. The A25A2 module is then replaced. After the replacement of the faulty A25A2 module, the technological procedure from Figure 7 is carried out again and the obtained results show that the device is not defective. The results of the testing performed by the TEST station are the same as the results shown in Table 1. The defective A25A2 module is sent for repair to a higher level of maintenance. Conclusion The paper shows an improved model of the technology of intermediate-level maintenance of RRDs, implemented by the SA logistics battalions. Based on the examination of the proposed model of the technology of corrective maintenance, it is concluded that the model, together with the proposed model of RRD defect detection algorithm, allows fast and safe operation during intermediate-level maintenance of this type of RRDs. Based on the research results, the following conclusions are drawn: - the improved model of the technology of intermediate level maintenance has been successfully implemented in the process of preventive and corrective maintenance of RRDs, - the model of the technological process is tailored to the training level of qualified personnel and to the maintenance equipment owned by logistics battalions, - the implementation of the RRD defect detection algorithm model in the process of corrective maintenance proved to be successful which confirmed the validity of the proposed model, - the answers to the questions on technology are provided and they are an integral part of the production process for intermediate-level maintenance, - quick implementation of corrective maintenance is facilitated which increases RRD operability and decreases the mean time of corrective maintenance, - it is explicitly defined which RRD integral modules can be changed at intermediate-level maintenance during the implementation of corrective maintenance, - aggregate replacement of RRD component modules during corrective maintenance considerably accelerates the process of maintenance and reduces the mean time of corrective maintenance, thus increasing the operability of the unit, - reliable defect detection of a device is achieved as well as the reliability of the device. The improved model of the technology of intermediate-level maintenance allows proper performance of maintenance personnel, significantly reducing the time of failure and increasing the reliability of the RRD device, as well as the reliability of the technical operations of overhaul. This method of determining the model of maintenance techniques can also be applied to other telecommunication devices in the Army of Serbia.